Entropy beyond the desert: Journey and otherness in "2666" (2004) by Roberto Bolaño - Medici, Matías Esteban (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Through this work I investigate the different forms of travel that occur in Roberto Bolaño’s 2666 (2004) -from a scheme based on various authors and a previous historical introduction- and on relationships with otherness, taking into account the definitions of Tzvetan Tódorov, since he have investigated this matter. I focus mainly on the first "novel" that composes the work, "The part about the critics", because typologies are deployed more intensely ther. Later, I also talk about exile in "The part about Amalfitano" and, finally, I explore some aspects of the inner journey in "The part of Fate".